The Aesthetics of Arabic Calligraphic and Islamic Formations in the Curtain of the Door of Kaaba: A Critical Artistic Study - Duaa Alashari; Abdelaziz Berghout (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The Kaaba's covering carries inherited aesthetics with an ancient historical and cultural character. The curtain for the door of the Holy Kaaba is an integral part of the design of the Kiswa of the Holy Kaaba, as it covers the door of the Holy Kaaba. The door curtain of the Holy Kaaba is considered an immortal and unique Islamic artistic painting in terms of the uniqueness of its design. Therefore, this study aims to apply the Western theory of art criticism (Feldman) to Arabic calligraphy and the calligraphic formations embodied in the curtain of the door of the Holy Kaaba to demonstrate aesthetic and artistic design values. The approach followed in this study is Feldman's approach to art criticism. Feldman's methodology is considered a systematic and integrated critical methodology for describing and analyzing artworks. In addition, this methodology enhances the aesthetic experience to understand art, its dimensions and value. The tool used in the study is observation. The study population consists of linear and decorative units with multiple styles. The study concluded that the curtain of the door of the Holy Kaaba is characterized by an abundance of calligraphic formations and compositions and Islamic decorative plant units.